2017
DOI: 10.1051/matecconf/201713801014
|View full text |Cite
|
Sign up to set email alerts
|

Study of Volcanic-Ash-Impregnated-Bacteria Filler to the Compressive Strength of Concrete

Abstract: Abstract. Technology of concrete has been advanced recently to improve the properties of concrete. Utilization of ash as the substitute of cement or filler of concrete also indicates good result in compressive strength concrete in certain amount. Harnessing the bacteria for self-healing concrete has also been successfully performed in order to maintain the destruction of the concrete by itself. Past research indicated that bacteria can be beneficiary to improve the compressive strength, absorption, permeabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“… Encapsulation in special minerals -diatomaceous earth (DE), zeolite [13,14,26,38]  Encapsulation in nanomaterials -graphene nanoplatelets (GNP), granular activated carbon (GAC), iron-oxide nanoparticles (IONPs) [3,13,29,41,42].  Encapsulation in cementitious materials-Metakaolin-geopolymer coating, limestone powder (LSP), calcium sulphoaluminate powder (CSA), volcanic ash [13,15,30,31,43].  Encapsulation in waste-derived biomass -biochar [16,17] Self-healing of cracks increases the toughness of concrete structures through the autogenous healing properties of cemented materials.…”
Section: Effect Of Bacterial Encapsulation On Crack Widthmentioning
confidence: 99%
See 1 more Smart Citation
“… Encapsulation in special minerals -diatomaceous earth (DE), zeolite [13,14,26,38]  Encapsulation in nanomaterials -graphene nanoplatelets (GNP), granular activated carbon (GAC), iron-oxide nanoparticles (IONPs) [3,13,29,41,42].  Encapsulation in cementitious materials-Metakaolin-geopolymer coating, limestone powder (LSP), calcium sulphoaluminate powder (CSA), volcanic ash [13,15,30,31,43].  Encapsulation in waste-derived biomass -biochar [16,17] Self-healing of cracks increases the toughness of concrete structures through the autogenous healing properties of cemented materials.…”
Section: Effect Of Bacterial Encapsulation On Crack Widthmentioning
confidence: 99%
“…This healed crack width was largest in comparison to other encapsulation materials. For some bacterial carriers, the healed crack width was not investigated but their effect on bacterial spores were studied [27][28][29][30][31]. Table 2 represents the type of bacterial carrier used by the authors and the corresponding maximum completely healed crack width.…”
Section: Effect Of Bacterial Encapsulation On Crack Widthmentioning
confidence: 99%
“…Microorganisms, including bacteria, fungi, and algae, responsible for the production of biominerals such as carbonate, silicate, and calcium phosphate [2][3][4] are useful as concrete filler. Bacteria from the genus Bacillus and Sporosarcina are one of the most widely used that has the ability to tolerate high pH, temperature, alkaline conditions, and live inside the concrete [5,6]. It is caused by a precipitate ion of CaCO 3 , from converting urea into ammonium and carbonate [7] and change the properties of the concrete mixtures and soil structures [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This type of bacteria forms endospores [10,11], so that it can survive without nutrients and water for hundreds of years [12]. The utilization of bacteria as the healing agent in concrete mixture to form self-healing concrete has been widely investigated [1,5,6,[12][13][14][15]. It is found that the calcium carbonate as microbes product, not only for healing the micro cracks, but also responsible to change the properties of the concrete mixtures [6].…”
Section: Introductionmentioning
confidence: 99%